2020
DOI: 10.48550/arxiv.2003.06459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semi-relativistic (e,2e) study with twisted electron beam on Cu and Ag

Aditi Mandal,
Nikita Dhankhar,
Didier Sébilleau
et al.

Abstract: In this communication, we report our calculations of Triple Differential Cross-Section (TDCS) for relativistic (e,2e) with twisted electron beam on heavy atomic targets, namely Cu, Au and Ag, in coplanar asymmetric geometry mode. The formalism has been developed in the first Born approximation using the Dirac plane wave as well as the twisted electron wave for the incident electron to study the effect of various parameters of the twisted electron on the relativistic (e,2e) process. We use Dirac plane wave, sem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The results indicated a shift in the binary and recoil peak for twisted electron cross-sections from their plane wave locations due to the projectile's transverse momentum components. The recent study by showed the dependence of the Total Angular Momentum (TAM) number (m), and opening angle (θ p ) on the angular profile of the TDCS and spin asymmetry for the relativistic electron impact ionization of the heavy atomic targets [43]. Furthermore, Dhankhar et al [44] studied theoretically the double ionization of He atom in θ -variable and constant θ 12 mode for the twisted electron incidence.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated a shift in the binary and recoil peak for twisted electron cross-sections from their plane wave locations due to the projectile's transverse momentum components. The recent study by showed the dependence of the Total Angular Momentum (TAM) number (m), and opening angle (θ p ) on the angular profile of the TDCS and spin asymmetry for the relativistic electron impact ionization of the heavy atomic targets [43]. Furthermore, Dhankhar et al [44] studied theoretically the double ionization of He atom in θ -variable and constant θ 12 mode for the twisted electron incidence.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated a shift in the binary and recoil peak for twisted electron's crosssections from their plane wave locations due to the projectile's transverse momentum components. The recent study by Mandal et al (2020) showed the dependence of the TAM number (m) on the angular profile of the TDCS and spin asymmetry for the relativistic electron impact ionization of the heavy atomic targets [54]. Furthermore, Dhankhar et al [55] studied theoretically the double ionization of He atom in θ-variable and constant θ 12 mode for the twisted electron incidence.…”
Section: Introductionmentioning
confidence: 99%
“…We are not presenting the results of our calculations of the elastic cross-section for H 2 molecule for brevity. We have also compared our calculation of the (e,2e) process on the hydrogen atom for the twisted electron with the one reported by Harris et al (2019) [54] treating the ejected electron as plane wave. We confirmed that our calculations also reproduce the results of Harris et al for an impact energy, E i = 1 keV and E e as 20 eV, 50 eV and 100 eV for θ s = 10 mrad with different values of θ p , i.e.…”
Section: Angular Profiles Of the Tdcs For Twisted Electron Beammentioning
confidence: 93%
“…The results indicated a shift in the binary and recoil peak for twisted electron's cross-sections from their plane wave locations due to the projectile's transverse momentum components. The recent study by Mandal et al (2020) showed the dependence of the TAM number (m) on the angular profile of the TDCS and spin asymmetry for the relativistic electron impact ionization of the heavy atomic targets [54]. Furthermore, Dhankhar et al [55] studied theoretically the double ionization of He atom in θvariable and constant θ 12 mode for the twisted electron incidence.…”
Section: Introductionmentioning
confidence: 99%